A shape-independent approach to modelling gear tooth spalls for time varying mesh stiffness evaluation of a spur gear pair. (1st April 2019) - Luo, Yang; Baddour, Natalie; Liang, Ming
Highlights: A shape-independent method was proposed to model tooth spalls. The proposed method utilizes defect ratios to model the features of tooth spalls. The proposed method is applicable to model different types of gear tooth spalls. The proposed method is convenient and straightforward. Abstract: Accurately evaluating the gear mesh stiffness with tooth fault(s) plays an important role in gear dynamic simulations. Common approaches to evaluating the gear TVMS with spall assume a specific geometry (rectangular, round, elliptical, V-shape etc.) to approximate the features of the spall. The accuracy of geometry-based methods on modeling gear tooth spall depends on how close the utilized geometry is to the actual shape of the spall. In practice, gear tooth spalls often occur in very irregular shapes and may also have randomly distributed features under multi-spall conditions. Due to shape irregularities and uncertainties in their distribution, it is often difficult to apply existing methods to accurately evaluate gear TVMS with spalls as observed in practice. To address these shortcomings, this paper proposes a shape-independent method to model tooth spall(s) based on defect ratios instead of a specific geometry. The proposed method is applicable to tooth spalls of various sizes, shapes, numbers and distribution conditions, and thus is capable of modeling any kind of tooth spall. A powerful advantage of the proposed method is that to change the type of spall being modelled, only the functions of the defect ratios need to be modified rather than the entire algorithm. Therefore, the proposed method is general in nature and much easier to implement in practice. The effectiveness of the proposed shape-independent approach to modelling different kinds of tooth spalls is validated by finite element results.